Morphology and Seasonal Distributions of External Myiasis Flies Determined in Elazi? Province - Şaki, Cem Ecmel; Özer, Edip (My University, 1999)
A study was carried out on morphology and seasonal distribution of myiasis flies in Elazi? and its districts (Sivrice, Kovancilar, Baskil and Salkaya) in 1994-1995. Putrified meat, liver and spleen pieces were used as baits to attract and congregate myiasis flies. In addition the baits were treated with Golden Malrin to kill the attracted flies for collection. Thus a total of 10440 myiasis flies were collected from the study sites. They were composed 7989 (76.52%) Lucilia sericata, 35 (0.34%) L. caesar, 540 (5.17%) Calliphora vicina, 46 (0.44%) C. vomitoria, 1416 (13.56%) Chrysomyia albiceps, 3 (0.03%) Wohlfahrtia magnifica. 233 (2.23%) Sarcophaga haemorrhoidalis and 178 (1.70%) S. carnaria. The examination of flies showed that 9490 (90.90%) of them were females and remaining 950 (9. 10%) were males. W. magnified comprised only female whereas other species were composed of both females and males. Seasonal activities of the flies ranged from April to October. They occured in April, increased in number until May or June and decreased gradually until October. The flies were not observed in January, February, March, November and December 1994 and 1995, whereas flies were present at the maximum rate in May 1994 (20.92%) wherein, the average temperature was 17.9°C, the relative humidity 52.8% and the rainfall 24.4 mm3, according to meteorological details, and in June 1995 (24.6%) in which these values were 21.4°C, 43.4% and 10.7 mm3, respectively.
Elazi? ve Yöresinde Tespit Edilen Eksternal Myiasis Sineklerinin Morfolojileri ve Mevsimsel Da?ilimlari
Keywords: Elazi?; External Myiasis Flies; Morphology; Seasonal Distribution